Tests of Kansas cements and concretes - Thummel, Claud B. (My University, 1905)
Introduction: In all, modern building and construction work there is a demand for some material which will not soon wear out, one which is also fire proof and something which is also water proof. To answer all of these requirements, many things have been tried but none seem to stand the tests which the ordinary cement and concrete do. When pure or nearly pure limestone is calcined to drive off the: carbondioxide an oxide of lime commonly called quicklime is formed, which upon the addition of water will slack causing heat and resulting in a fine powder and if still more water be added resulting in a paste from which is made the: common mortar which will set only in air. By setting is meant that process which a substance undergoes after being mixed with another, usually water, before it attains its final form and hardness. If the original limestone contains also a small per cent of clay or silica the product will slack due to the free lime present and in addition will set under water. This is called hydraulic Hydraulic cements differ from limes in that they contain enough impurities that the slacking is negligable and that they will set under water. Hydraulic cements may be divided into three classes as follows: (l) Natural (2) Portland (3) Pozznolana. Which will be taken up in order? The first two differ from the third in that they require; a process of calcination. NATURAL CEMENTS. Natural cement is made from a natural carbonate or magnesian limestone. The stone is calcined or burned at low temperature to a clinker; this is crushed and ground very fine. The product is of a brownish color and is what is commonly called "Natural Cement" by the commercial world.
Citation: Thummel, Claud B. Tests of Kansas cements and concretes. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Natural Cement; Portland Cement; Pozznolana; Theses